2007
DOI: 10.1089/pho.2007.1098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Laser Therapy on Inflammatory Reactions during Wound Healing: Comparison with Meloxicam

Abstract: LLLT improves the quality of histologic repair and is useful during wound healing. However, with the methods used in this study the laser energy did not minimize tissue inflammatory reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 14 publications
2
36
0
5
Order By: Relevance
“…In addition, this technique is non-invasive, nonpharmacological, and has few side effects (MEDEIROS et al, 2010). There is still no consensus on the antiinflammatory activity of PBMT because previous studies have indicated a possible anti-inflammatory activity at the initial stages of the wound-healing process (MEDRADO et al, 2008;VILELA et al, 2012;, whereas other authors did not detect this activity (VIEGAS et al, 2007). There is also the report of the modulation of inflammatory mediators (FIORIO et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this technique is non-invasive, nonpharmacological, and has few side effects (MEDEIROS et al, 2010). There is still no consensus on the antiinflammatory activity of PBMT because previous studies have indicated a possible anti-inflammatory activity at the initial stages of the wound-healing process (MEDRADO et al, 2008;VILELA et al, 2012;, whereas other authors did not detect this activity (VIEGAS et al, 2007). There is also the report of the modulation of inflammatory mediators (FIORIO et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The antiinflammatory action of PBMT in the early stages of tissue repair is associated with the decrease in the number of inflammatory cells (MEDRADO et al, 2008;VILELA et al, 2012). However, some studies did not find any difference in the number of polymorphonuclear cells between the group treated with PBMT and the control group and consequently did not corroborate this anti-inflammatory activity (VIEGAS et al, 2007). Therefore, there is no consensus on the antiinflammatory potential of PBMT in skin wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…11,20,21,[24][25][26][27][28][29] A growing body of evidence suggests that LPT has anti-inflammatory action and accelerates tissue repair. 18,19,21,22 However, these effects are dependent on wavelength, output power, 28,35 and energy density.…”
Section: Discussionmentioning
confidence: 99%
“…22 The effects of LPT on the healing process of skin wounds have been studied, particularly using the dorsum skin model to investigate the effect of different irradiation parameters. 11,20,21,[23][24][25][26][27] A growing body of evidence suggests that LPT has anti-inflammatory action and accelerates tissue repair. 18,19,21,22 However, these effects are dependent on irradiation parameters such as wavelength, output power, 28,29 and energy density.…”
Section: Introductionmentioning
confidence: 99%
“…Novas possibilidades terapêuticas estão sendo preconizadas utilizando a terapia laser de baixa intensidade (LLLT) no processo de reparo tecidual. Esta terapia demonstra ser um recurso eficaz na diminuição do tempo de reposição tecidual, ou seja, melhora a qualidade da reparação tecidual e acelera o processo de cicatrização [6][7][8][9] . Modelos experimentais de diabetes em murinos estão sendo amplamente estudados a fim de esclarecer o mecanismo fisiopatológico da doença.…”
Section: Introductionunclassified